2015
DOI: 10.3732/ajb.1400344
|View full text |Cite
|
Sign up to set email alerts
|

Chenopodium polyploidy inferences from Salt Overly Sensitive 1 (SOS1) data

Abstract: We infer that the two polyploid lineages arose independently and that each lineage may have originated only once. The American diploid, C. standleyanum, was identified as the closest living diploid relative of the A genome donor for American tetraploids, including domesticated C. quinoa, and is of potential importance for quinoa breeding. The east Asian diploid species, C. bryoniifolium, groups with American diploid species, which suggests a transoceanic dispersal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 42 publications
(46 reference statements)
0
45
0
1
Order By: Relevance
“…Single-gene sequencing studies previously identified pools of North American and Eurasian diploids as candidate sources of the A and B sub-genomes, respectively [20][21][22] , with hybridization occurring somewhere in North America. To understand genome structure and evolution in quinoa further, we sequenced, assembled, and annotated the A-genome diploid C. pallidicaule (commonly called cañahua or kañiwa) and the B-genome diploid C. suecicum 21 (Fig.…”
Section: Evolutionary History Of Quinoamentioning
confidence: 99%
“…Single-gene sequencing studies previously identified pools of North American and Eurasian diploids as candidate sources of the A and B sub-genomes, respectively [20][21][22] , with hybridization occurring somewhere in North America. To understand genome structure and evolution in quinoa further, we sequenced, assembled, and annotated the A-genome diploid C. pallidicaule (commonly called cañahua or kañiwa) and the B-genome diploid C. suecicum 21 (Fig.…”
Section: Evolutionary History Of Quinoamentioning
confidence: 99%
“…In hexaploid wheat, transcriptome assemblies in ancestral diploid species were used to classify the genes predicted from a de novo genome assembly into the A, B, and D genomes 72 . This was not possible in quinoa because the donor diploid species of the B-genome has yet to be identified, 23 and no genome or transcriptome data of the A-genome species were available. Nevertheless, the fact that we could identify several putative homeologous genes suggests that we were successful in capturing the two subgenomes at least to a certain extent.…”
Section: Resultsmentioning
confidence: 99%
“…Quinoa is an allotetraploid species (2 n = 4 x = 36 with a genome size of 1,448 Mbp) 21 , 22 that consists of two distinct genomes, A and B 23 . Genetic mapping of quinoa has been conducted using amplified fragment length polymorphism (AFLP) markers, 1 simple sequence repeat (SSR) markers, 1 and array-platform markers 24 .…”
Section: Introductionmentioning
confidence: 99%
“…The SOS1 gene tree resolves the Chenopodium species studied in three clades, the first comprising of 'Vulvaria' and 'Auricomum' clade, the second clade A of American species and the third large clade is divided into B, C and D clades comprising of polyploids and one Eurasian C. ficifolium. Two distinct lineages of alloploids have been identified of which one is of American tetraploids with homeologs in A and B clades while Eastern Hemisphere hexaploids including C. album (6x) had three distinct genomes with one homeolog each of B, C and D clades [27].…”
Section: Genome Analysis and Origin Of Polyploidy Taxamentioning
confidence: 99%
“…Further evidence for the Eastern Hemisphere hexaploids comprising of three different genomes has come from phylogeny based on two introns of single copy nuclear Salt Overly Sensitive 1 (SOS1) locus [27]. The SOS1 gene tree resolves the Chenopodium species studied in three clades, the first comprising of 'Vulvaria' and 'Auricomum' clade, the second clade A of American species and the third large clade is divided into B, C and D clades comprising of polyploids and one Eurasian C. ficifolium.…”
Section: Genome Analysis and Origin Of Polyploidy Taxamentioning
confidence: 99%